PERBANDINGAN ARUS DAN TEGANGAN LARUTAN ELEKTROLIT BERBAGAI JENIS GARAM - Fitri Mah Bengi; Ayu Sri Wahyuni; Wahyu Syamsuryani; Dona Mustika (Jurnal Pendidikan Fisika dan Sains, 2019)
Electrolyte solution is a solution that can conduct electricity and NaCl solution is an example of a strong electrolyte solution. NaCl is a chemical compound of salt. On the market can be found many types of salt. In this research, the ratio of current and voltage of electrolyte solution obtained from various types of salt was obtained. This research was conducted by an experimental method using a simple electrical circuit. The purpose of this study is to find out how much current and voltage are produced in each salt, To find out if a salt water solution can turn on the lights. The results showed that the electric current which has the highest value is that of sea salt with the respective water volume 240 mL in 20, 40, 60, gr salt, wherein the current is obtained for 20 gr of current obtained 0.81 A, for 40 gr of current obtained 1.09 A, for 60grn of current obtained 1.16 A and the resulting voltage is the same as 001 volts where the higher the water content salt the salt water voltage is also higher. Then the electric current which has the lowest value is the dalfino salt and elephant salt with their respective volumes of water 240 mL of dalfino salt in 20 gr, 40 gr, 60 gr. For 20 grams of Dalfino and elephant salt a current of 0.33 A is obtained, for 40 grams obtained 0.44 A, for 60 grams obtained 0.65 A, and in the current elephant salt obtained in 20 gr, 40 gr, 60 gr, that is, for 20 grains a current of 0.24 A is obtained, for 40 grams a current of 0.52 A is obtained, for 60 grams a current is obtained currents 0.72 A. So, sea salt can produce high currents because sea salt contains sodium chloride, contains various minerals such as potassium, iron and zinc.